2020
DOI: 10.1186/s12890-020-01182-y
|View full text |Cite
|
Sign up to set email alerts
|

Supervised pulmonary hypertension exercise rehabilitation (SPHERe): study protocol for a multi-centre randomised controlled trial

Abstract: Background: Supervised cardio-pulmonary rehabilitation may be safe and beneficial for people with pulmonary hypertension (PH) in groups 1 (pulmonary arterial hypertension) and 4 (chronic thromboembolic disease), particularly as a hospital in-patient. It has not been tested in the most common PH groups; 2 (left heart disease), 3 (lung disease), or 5 (other disorders). Further it has not been evaluated in the UK National Health Service (NHS) outpatient setting, or with long-term follow-up. The aim of this random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…(9) However, there is ample evidence that physical activity can improve endothelial function, exercise capacity and quality of life in patients with chronic arterial disease and chronic left heart failure. (12) The results showed that in 6 minutes the patient was able to cover a distance of 315 meters. Then this distance is useful for determining the dose of rehabilitation carried out.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(9) However, there is ample evidence that physical activity can improve endothelial function, exercise capacity and quality of life in patients with chronic arterial disease and chronic left heart failure. (12) The results showed that in 6 minutes the patient was able to cover a distance of 315 meters. Then this distance is useful for determining the dose of rehabilitation carried out.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of exercise training on respiratory muscle strength has been investigated and resulted in a significant increase in VO2 at the anaerobic threshold, indicating an increase in respiratory muscle strength during exercise. (12) A meta-analysis that conducted exercise training studies in cases of chronic thromboembolic pulmonary hypertension (CTEPH) also provided significant results on quality of life where it was stated that physical function, general health perception and even mental health were significantly improved in patients with CTEPH. Exercise exercises combined with pulmonary hypertension-specific drug therapy has shown beneficial effects in patients with CTEPH.…”
Section: Discussionmentioning
confidence: 99%
“…The revised protocol was approved by the funder and independent committees. 39 The online SPHERe intervention was then tested in an internal pilot study.…”
Section: Adaptations Due To Covid-19 Pandemicmentioning
confidence: 99%
“…A separate process evaluation will assess programme acceptability amongst participants and practitioners. 39…”
Section: Intervention Fidelity: Practitioner Training and Quality Con...mentioning
confidence: 99%
“…One is about the safety, economic applicability, feasibility, and patient compliance of home-based ERT for PH patients, which is supervised by telehealth or distance-based programs [61]. Another one has included clinical deterioration time as the endpoint to evaluate the effectiveness of longterm ERT for PH patients as a routine treatment outside the hospital [62]. A survey composed of 280 physicians, including cardiologists, pulmonologists, rheumatologists, and general practitioners from 22 countries published in 2020, showed that 86% of physicians recommend ERT for patients with PH.…”
Section: Future Directionsmentioning
confidence: 99%